Biophysical Controls of Ecosystem‐Scale Methane Fluxes From a Subtropical Estuarine Mangrove: Multiscale, Nonlinearity, Asynchrony and Causality. Issue 6 (28th May 2022) - Liu, Jiangong; Valach, Alex; Baldocchi, Dennis; Lai, Derrick Y. F.
Abstract: Mangroves are complex ecosystems subject to periodic and irregular changes in meteorology, tides, water quality and biological factors. Methane dynamics in mangroves and their dependence on biogeochemical controls across scales are poorly characterized using traditional parametric statistics. We measured the ecosystem‐scale methane flux (FCH4 ) using an eddy covariance system in a subtropical estuarine mangrove for two years. A combination of nonparametric statistical approaches, including singular spectrum analysis and information theory, was used to isolate multiscale FCH4 variations and explore their variability and dominant controls at different time scales. FCH4 exhibited the largest variability at the diel scale (57%), followed by seasonal (25%) and multiday (18%) scales. Mutual information metrics suggested that variation in FCH4 was dominantly coupled to plant activities through synchronous processes at the diel scale. Moreover, fluctuations in atmospheric turbulence and soil temperature dominated multiday variation in FCH4 through asynchronous processes. Seasonally, soil temperature and water salinity were dominant variables leading to changes in FCH4 with a time lag of 12 and 17 days, respectively. Weak links between FCH4 and tidal heights were found across all the studied time scales. Transfer entropy metrics indicated that a super typhoon event substantially weakened causal links between biophysical variables and FCH4 by causing severe defoliation and disturbing the soil microbial community. The typhoon also temporarily decoupled the causal link between FCH4 and temperature. These findings call for the inclusion of the properties of scale emergence, nonlinearity, asynchrony and causality for comprehensively understanding and accurately predicting the interactions between mangrove FCH4 and its biophysical controls. Key Points: Plant activities dominated diel scale variability in methane fluxes driving both production and transport through synchronous processes Physical variables (such as temperature and salinity) dominated the long‐term variation in methane fluxes through asynchronous processes A super typhoon decoupled the causal link between methane fluxes and temperature